A Balto-Slavic key to the etymology of Tocharian B twār - Blažek, Václav (Baltistica, 2013)
From the point of view of word formation and semantics, it seems the Tocharian B adverb twār "for this reason, consequently" is etymologizable with help of the Balto-Slavic verb *tu̯erH- "to create, produce, form, compose; hold; continue" and its Slavic nominal derivatives as Old Church Slavonic tvorъ "act, deed", tvarь "creation, creating, making, deed, act; form, nature". The original starting point of the Tocharian word could be the loc. sg. *tu̯ōr-i of the root noun *tu̯ōr-.